Perancangan Resort Pantai Pendekatan Konsep Neo Vernakular di Pangandaran - Ahmad Aguswin; Dikri Muklis Pirdaus (Prosiding Sains dan Teknologi, 2022)
Pangandaran Beach is designated as one of the National Tourism Strategic Areas namely KSPN Pangandaran with an emphasis on the theme of tourism development based on local wisdom of local culture. In the current condition in Pangandaran dwellings In all Pangandaran destinations, the resort accommodation accommodation facilities are only 2 units, namely the beautiful resort and blue sea resorts, the decline in the image of tourist attractions due to the mushrooming of unfit residential places along the coast of Pangandaran, the absence of residential resorts that have complete facilities and infrastructure. Therefore a resort resort with a neo vernacular concept approach is needed to bring Sundanese culture that has complete facilities. While the translation analysis is done descriptively based on local existing conditions. So that it can produce neo vernacular building concepts that combine modern and traditional concepts that reflect Pangandaran culture. the concept used is the Sundanese architecture approach which applies Sundanese philosophical concepts in the form of the middle syneger, glass, uga, pamali and weak cai. Based on the observation that the resort area which is very suitable to be built is located in Wonoharjo Village, Pangandaran District, Pangandaran Regency, West Java Province. This location was chosen with consideration of the views directly overlooking the beach to the south and also located in the tourism center of Pangandaran Regency. Keywords: Resort, Neo Vernacular, Sundanese Architecture, and Pangandaran Beach